PENGARUH PERBEDAAN KONSENTRASI EMULGATOR PADA SEDIAAN LOTION EKSTRAK DAUN BIDARA (Ziziphus spina-christi L.) TERHADAP MUTU FISIK - Hamka, Zulfahmi; Muis, Nurul Ilmi (Akademi Farmasi Yamasi Makassar, 2025)
Bidara leaves contain many useful ingredients, including alkaloids, phenols, flavonoids, saponins, quercetin, and terpenoids and the leaves have the potential to act as natural antioxidants.To increase the utilization or use value of bidara leaves they can be mae into a preparation, namely lotion. The aim of this research is to make and test the quality of a physicalpreparation of lotion from bidara leaf extract (Ziziphus spina-christi L.). Bidara leaves were extracted using a maceration method using 96% ethanol solvent for 3x24 hours. This lotion preparation is made with varying concentrations of Anionic and Nonionic emulsifiers and then a physical evaluation is carried out including organoleptic tests, homogeneity tests, pH tests of the preparations, adhesion tests and spreadability tests. Based on the results of the research carried out, it can be concluded that differences in emulsifier concentration affect quality including organoleptics, adhesion, dispersion and pH. The results of the physical evaluation of lotion preparations in the organoleptic test were that F1 was brown, F2 was green, had a distinctive aroma, F1 preparation was thick, F2 was slightly thick and both textures were smooth. The lotion preparation was mixed homogeneously, the pH and adhesion tests met the standard requirements but the spreadability test did not meet the standard requirements.